2020
DOI: 10.1136/bmjebm-2020-111511
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of tests to detect the presence of SARS-CoV-2 virus, and antibodies to SARS-CoV-2, to inform COVID-19 diagnosis: a rapid systematic review

Abstract: ObjectivesWe undertook a rapid systematic review with the aim of identifying evidence that could be used to answer the following research questions: (1) What is the clinical effectiveness of tests that detect the presence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to inform COVID-19 diagnosis? (2) What is the clinical effectiveness of tests that detect the presence of antibodies to the SARS-CoV-2 virus to inform COVID-19 diagnosis?Design and settingSystematic review and meta-analysis of st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 61 publications
(123 reference statements)
1
87
0
6
Order By: Relevance
“…Coronavirus Disease (COVID-19) is an infectious acute respiratory syndrome caused by the virus SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) able to enter the human cells through the angiotensin-converting enzyme 2 (ACE2) receptor, like the SARS virus [1]. COVID-19 mainly affects Pharmaceuticals 2020, 13, 377 2 of 11 the lower respiratory tract and causes several flu-like symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronavirus Disease (COVID-19) is an infectious acute respiratory syndrome caused by the virus SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2) able to enter the human cells through the angiotensin-converting enzyme 2 (ACE2) receptor, like the SARS virus [1]. COVID-19 mainly affects Pharmaceuticals 2020, 13, 377 2 of 11 the lower respiratory tract and causes several flu-like symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…through the angiotensin-converting enzyme 2 (ACE2) receptor, like the SARS virus [1]. COVID-19 mainly affects the lower respiratory tract and causes several flu-like symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of these weaknesses, this systematic review has several offsetting strengths. It focuses on sample sets that have been taken at the same time, thus differing from other systematic reviews, 34 , 35 , 36 , 37 , 38 as well as a release from the Norwegian Institute of Public Health. ( https://www.fhi.no/globalassets/dokumenterfiler/rapporter/2020/saliva-sample-for-testing-sars-cov-2-infection-memo-2020.pdf , last accessed 12/14/2020) The total number of samples included in the meta-analysis is substantially greater than that of any idividual study based on simultaneous sample comparison, and allows for meta-analysis based sensitivity estimates.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential that the performance of newly developed POCT assays be thoroughly evaluated before use. Performance between different POCT assays varies greatly (see Supplementary Table 4 ) [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] ] with a range of different assay sensitivities. The meta-analysis by ML Bastos in July 2020 [ 3 ] showed that POCT assays up till April 2020 had varied sensitivities (36.4%–100%).…”
Section: Discussionmentioning
confidence: 99%